Pengaruh Media Dakota Terhadap Hasil Belajar Siswa Pada Materi KPK dan FPB di Kelas IV SD Negeri Kuta Japakeh Pidie Jaya - Sitti Sarah; Indah Surya Wati; Kamalliansyah Walil; Nur Ainun (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
There are still 40% of students who have not reached the KKM score on the subject matter, especially the KPK and FPB material, so researchers try to provide solutions by offering attractive learning media as an alternative to learning media. The media referred to in this research is Dakota media. The purpose of this study was to determine the effect of using Dakota media on student learning outcomes on the KPK and FPB materials in class IV SDN Kuta Japakeh Pidie Jaya. The approach in this research is quantitative. The sample in this study were all fourth grade students, amounting to 30 students consisting of 18 female students and 12 male students. The technique of collecting data uses tests, the data is analyzed using statistical formulas. The results showed that the learning media using Dakota media had an influence on student learning outcomes on the KPK and FPB material in class IV SDN Kuta Japakeh Pidie Jaya. The average value obtained is 80.25. the results of data processing t_count ≥ ttable, namely 11.18 ≥ 1.699, thus H_o is rejected and H_a is accepted. So based on the H_o decision criteria, namely reject H_o and accept H_ (a.) So it can be concluded that Dakota media has an effect on student learning outcomes on KPK and FPB material in class IV SDN Kuta Japakeh Pidie Jaya